Criminalistic and Criminal-Legal Aspect of Collecting and Evaluating Evidence in the Processing of the Criminal Offense of Money Laundering Before the Court of BIH - Dautbegović, Almin; Ahmić, Elmedin (Kriminalističke teme, 2013)
Summary Ingenuity of people who deal with money laundering has no limit. Therefore, for those who are required to undertake actions and measures to detect and prosecute money laundering, sometimes is extremely difficult to recognize this crime spree. In enumerating the taxpayers under the Law on the Prevention of Money Laundering in B&H, not incidentally, in the first place are banks and other financial organizations. Banking business, and on one hand, means absolute confidentiality and protection of customer data and the confidentiality of roles, on the other hand, exposure to a number of risks of money laundering activities. Prosecution and on convictions for money laundering in the Court of Bosnia and Herzegovina, which have been made so far and the ones that are up to date, give a clear sign that the fight against this form of crime does not stop, but that the state authorities are aimed to combat this form of crime. On the basis of previous judgments, it can be stated that there is a decisive fight against money laundering. On the other hand, there are certain disadvantages in overall crime policy and in the ways of collecting and evaluating evidence when it comes to this crime. This paper gives the overwiev of money laundering activities, in terms of crime prevention work, collection of evidence, criminal justice aspect of legality, as well as evaluation and prosecution of money laundering in B&H.